2022
DOI: 10.20520/jel-kep.2022.2.1
|View full text |Cite
|
Sign up to set email alerts
|

The Parliament about the Clouds: Motivational Factors of Metaforic Hybrids

Abstract: One of the most known visual metaphors is hybrid (Forceville 2002), a conceptual process in which the visual target and the visual source domains are integrated into one entity providing a high potential of incongruency (e.g., a cat with elephant ears). Previous research mostly focused on hybrids in isolation and studied their physical features as potential motivational factors behind them. The present paper aims to systematically investigate the hybrids with their motivational factors in discourse and provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…31 For the detailed discussion of the motivational factors in visual metaphorical hybrids and their relations to metonymical hybrids, see Virág (2022b). It provides a typology of the potential motivational factors by exemplifying each with analysis of hybrids including the PARLIAMENTARY DOME as a metaphorical target domain.…”
Section: The Typology Of Metaphor In Visual and Multimodal Discoursementioning
confidence: 99%
See 1 more Smart Citation
“…31 For the detailed discussion of the motivational factors in visual metaphorical hybrids and their relations to metonymical hybrids, see Virág (2022b). It provides a typology of the potential motivational factors by exemplifying each with analysis of hybrids including the PARLIAMENTARY DOME as a metaphorical target domain.…”
Section: The Typology Of Metaphor In Visual and Multimodal Discoursementioning
confidence: 99%
“…During the first period, it is stated that within the metaphorical source domain of PHYSICAL CONFLICT, we can never see real physical clash or brawl among the politicians, but instead, 135 In Virág (2021aVirág ( , 2022b, the metaphoric representation of the Parliament was studied in political cartoons (retrieved from the satirical magazine Ludas Matyi) from the period of 1989 and 1990. It was shown that in 1989, such domain-level metaphors were dominant as ENTERTAINMENT and FAMILY, while in 1990, which was the year of election FIGHT, came to the fore.…”
Section: Domain-level Metaphoric Sources In Various Periods Of Democracymentioning
confidence: 99%